Integrating Corporate Governance Practices into New Financing Projects and Executive Pay Structures - Dewi, Mutia Sari (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to explore the integration of corporate governance practices into new financing projects and executive pay structures, highlighting their impact on organizational performance, transparency, and stakeholder trust. It addresses the growing need for robust governance mechanisms to align executive incentives with long-term value creation and effective decision-making in financing projects. Research Design and Methodology: A quantitative descriptive research design was employed, utilizing survey instruments, statistical analysis, and regression modeling to examine the integration of governance practices across diverse corporations. The study focused on the prevalence, determinants, and outcomes of governance integration in financing projects and executive compensation structures. Findings and Discussion: The findings reveal that robust corporate governance mechanisms significantly influence firms' financing decisions and executive compensation structures. Effective governance practices enhance transparency, accountability, and risk management, leading to lower financing costs, greater investor confidence, and improved project outcomes. The study also highlights the role of performance-based executive compensation schemes in aligning executive incentives with shareholder interests, fostering long-term value creation. Implications: The research underscores the importance of integrating corporate governance practices into financing and compensation frameworks to enhance organizational performance and stakeholder trust. It offers practical insights for policymakers, practitioners, and scholars on developing governance mechanisms that ensure prudent decision-making and value optimization. The findings advocate for continuous improvement in governance practices to meet evolving regulatory, shareholder, and societal expectations.